2010
DOI: 10.1097/sla.0b013e3181e6239e
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Da Vinci Surgical System in Abdominal Surgery Compared With That of Laparoscopy

Abstract: The publications reviewed revealed DVSS to offer certain advantages with respect to Heller myotomy, gastrectomy, and cholecystectomy. However, these results should be interpreted with caution until randomized clinical trials are performed and, with respect to oncologic indications, studies include variables such as survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
200
0
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 359 publications
(222 citation statements)
references
References 44 publications
7
200
0
15
Order By: Relevance
“…Interestingly, in the Chicago group's study 10, the cold ischemia time was 47 min longer in the robotic group than the open surgery group. Based on our experience and the results of large meta‐analyses and series, the use of robotic assistance is likely responsible for an increase in operative time, as compared to open or laparoscopic surgery 17, 18, 19, 20, 21. We thus believe that a longer anastomosis time and uncontrolled kidney rewarming are valid concerns in robot‐assisted kidney transplantation.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, in the Chicago group's study 10, the cold ischemia time was 47 min longer in the robotic group than the open surgery group. Based on our experience and the results of large meta‐analyses and series, the use of robotic assistance is likely responsible for an increase in operative time, as compared to open or laparoscopic surgery 17, 18, 19, 20, 21. We thus believe that a longer anastomosis time and uncontrolled kidney rewarming are valid concerns in robot‐assisted kidney transplantation.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple studies have demonstrated that the outcomes of RC are similar to LC with regards to initial hospitalization as well as 30-day complications related to the index procedure (30). While there is some evidence that RC is safe with satisfactory patient outcomes at 3-year follow-up (31), there is limited reporting of long term outcomes.…”
Section: Outcomes Of Robotic Cholecystectomy: Safety and Patient Satimentioning
confidence: 97%
“…[5] Both laparoscopic and robotic-assisted esophageal myotomy are comparable in terms of feasibility, safety, and longterm symptomatic relief. [24,25] However, robotic surgery is superior in terms of mucosal perforation. In a comparative study of 121 myotomies in adults, there were no cases of mucosal perforation in the robotic myotomy group, but mucosal perforation occurred in 16% of patients in the laparoscopic group.…”
Section: Discussionmentioning
confidence: 99%